Utilization of Fiber Optic Network in Support of Voip Infrastructure: Case Study of Implementation at State Polytechnic of Malang - Andhini Lionita Prasetya; Farida Arinie; Muhammad Syirajuddin S (Westscience Press, 2024)
In the modern era, the need for fast and high-performance communication is crucial to support the advancement of information technology. Voice Over Internet Protocol (VoIP) enables voice transmission over IP networks, offering cost savings compared to conventional telephony. The State Polytechnic of Malang (Polinema) transitioned from a conventional Private Automatic Branch Exchange (PABX) system, which is now difficult to maintain, to a custom Internet Protocol Private Branch Exchange (IP PBX) system that is more flexible and integrated with existing data networks. The use of Ethernet Passive Optical Network (EPON) in VoIP infrastructure offers benefits such as high capacity, quality VoIP data transmission, energy efficiency, and reduced operational costs. This combination of optical fiber (EPON) and VoIP allows Polinema to create a more efficient and reliable communication solution, enhancing accessibility and the quality of the learning experience. This research is also expected to inspire other educational institutions to adopt similar innovations.